Literary Psychological Analysis of the Novel entitled “Laut Bercerita” by Leila S. Chudori - Alya Selsa Meyriska (Pedagogy Review, 2023)
Abstract: Literary work contains meaning in it, not just a form of work that contains aesthetics. Poetry means imaginative literary works, the words used are arranged using aesthetic and simple words, readers who do not have the knowledge of analyzing poetry will have difficulty understanding the meaning of the poetry they read. The writer is interested in analyzing the poem "Rahasia Hujan" by Heri Isnaini, because this poem has lyrics formed from a unique and simple language structure but has a broad meaning and makes readers interested in his work. Keywords: poetry, mimetic, literacy psychological analysis.